2009
DOI: 10.1080/21650993.2009.9756062
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving in the Pacific Rim A Comparison of Asian and Non-Asian Caregiving Experiences

Abstract: This study compares the results of two surveys of informal caregivers conducted in California and Hawaii (N = 1677) to determine if there is a uniquely asian model of caregiving. Differences between asian and non-asian caregivers were found in the percentage of male caregivers, the impact of caregiving personally and on the family, and on employment. Furthermore, in multivariate analysis, being of asian origin retained significance in predicting both positive and negative caregiver outcomes. This study sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similarly, Anngela-Cole and Hilton (2009) found that Caucasian Americans felt greater obligation toward their parents and had more positive attitudes toward caregiving than Japanese Americans. Further, in a sample of family caregivers, non-Asian Americans were more likely to say that caregiving has positive (personal and familial) impact on them than the Asian Americans (Arnsberger et al, 2009). Furthermore, the history of Confucian principles in the East Asian cultures and conception of joint family system in South Asian cultures impel individuals to respect, obey, and care for their elderly family members (Sung, 1995;Koyano, 1996;Singh, 2005), North Americans who do not abide to Confucian principles may be compelled to love and care for their senior parents with different motives.…”
Section: Filial Piety and Care For Elderly Parentsmentioning
confidence: 94%
“…Similarly, Anngela-Cole and Hilton (2009) found that Caucasian Americans felt greater obligation toward their parents and had more positive attitudes toward caregiving than Japanese Americans. Further, in a sample of family caregivers, non-Asian Americans were more likely to say that caregiving has positive (personal and familial) impact on them than the Asian Americans (Arnsberger et al, 2009). Furthermore, the history of Confucian principles in the East Asian cultures and conception of joint family system in South Asian cultures impel individuals to respect, obey, and care for their elderly family members (Sung, 1995;Koyano, 1996;Singh, 2005), North Americans who do not abide to Confucian principles may be compelled to love and care for their senior parents with different motives.…”
Section: Filial Piety and Care For Elderly Parentsmentioning
confidence: 94%
“…Further, in a sample of caregivers, Asian Americans were less likely to refer to filial values than their U.S. counterparts (Arnsberger, Chang, & Mensendiek, 2009). Elmelech (2005) examined attitudes towards family obligations and found that compared to a U.S. sample, Japanese respondents were less likely to agree that children should make sacrifices to support their parents.…”
Section: Filial Pietymentioning
confidence: 93%